2003
DOI: 10.1117/12.505553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crystal surface roughness on the angular spread of x-ray diffracted beam

Abstract: One of the factors influencing the focus size in diffractive-refractive optics is the quality of diffracting surface. If the surface is uneven, then the diffraction at each point of the surface is a combination of an asymmetric and inclined diffraction (general asymmetric diffraction). This somewhat deviates and spreads the diffracted beam. The integration over the surface hit by an incident beam gives the angular spread of the diffracted beam. It is shown that in some cases (highly asymmetric, highly inclined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This approach is obviously justified when the size of the unevenness structures is much larger than the wavelength. Nevertheless, as was shown in [9] and will be shown later, this theoretical model, together with the surface profile measurement (e.g. by alpha-step) can predict the spread of the diffracted beam.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…This approach is obviously justified when the size of the unevenness structures is much larger than the wavelength. Nevertheless, as was shown in [9] and will be shown later, this theoretical model, together with the surface profile measurement (e.g. by alpha-step) can predict the spread of the diffracted beam.…”
Section: Introductionmentioning
confidence: 69%
“…Then the integration was performed over all these deviations by using MATLAB and by taking into account the distribution function. In [9] all calculations were performed for white impinging beam with the divergence of 10 µrad × 10 µrad and for the diffraction on a Si(111) single crystal. It was shown that when the diffracted beam forms small angle with the surface (e.g.…”
Section: Calculation and Measurement Of The Spread Of Diffracted Beammentioning
confidence: 99%
See 2 more Smart Citations